PEMBUATAN MALTODEKSTRIN DARI PATI BIJI NANGKA (Artocarpus heterophyllus) DAN APLIKASINYA SEBAGAI ENKAPSULAN ASAP CAIR - , CHAIRUNISA CHAYATINUFUS; , Prof. Dr. Ir. Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Jackfruit seed is a solid waste that has a high starch content. The starch from jackfruit seed can be processed into maltodextrin using partially hydrolysis by enzymes Î± â amylase. Maltodextrin can be applied as encapsulant. One of products that needs to be encapsulated is liquid smoke. Liquid smoke have a volatile compounds such as phenols, carbonyls and acids. Volatile compounds in liquid smoke can evaporate and easily damaged. Therefore it needs encapsulant. This research was aimed to know the potential of jackfruit seeds as enkapsulant in liquid smoke microencapsulation and to know the comparison effect among soluble solids of liquid smoke redistillate and maltodextrin on the efficiency and the characteristics of microcapsules produced. In this research, jackfruit seed starch was hydrolyzed with different variation of time. The variations were 60, 90 and 120 minutes. Maltodextrin which was made with selected hydrolysis time, were analyzed dextrose equivalent and moisture content. This maltodextrin was used for liquid smoke microencapsulation. The microencapsulation used spray drying method with the ratio between soluble solids of liquid smoke redistillate and maltodextrin were 1:2, 1:3,5 and 1:5. The efficiency and characteristics of microcapsules that was produced would be analyzed such as content of phenol, content of acid, particle size, moisture content and product recovery.Microcapsule that the highest efficiency would be analyzed dispertion rate, morphology and compounds profile. The result show that the highest solubility is the maltodextrin which had hydrolyisis time for 120 minutes. The ratio variations between soluble solid of liquid smoke redistillate and maltodextrin affected the efficiency and characteristics of liquid smoke microcapsules except moisture content of microcapsule. The more ratio of maltodextrin were added, it will increased of efficiency microcapsule, content of acid levels and product recovery, but content of phenol levels and particle size is were lower.